PENGARUH PENERAPAN MEDIA E-BOOK INTERAKTIF BERBASIS CANVA TERHADAP KECERDASAN EMOSIONAL WARGA BELAJAR DI LEMBAGA PELATIHAN MORALITAS BUDI PEKERTI BANGSA INDONESIA - Jelita Tessalonika; Fauzi Kurniawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study addresses the low levels of emotional intelligence among learners at the Indonesian Nation's Character Moral Training Foundation, which stems from abstract, one-way moral learning methods that fail to foster emotional regulation. The purposes of this study are to describe the implementation of Canva-based interactive e-book media, determine learners' emotional intelligence levels, and ascertain the extent of the interactive e-book's influence as an instructional stimulant on learners' emotional intelligence. This study is a quantitative research employing a quasi-experimental approach with a One-Group Time Series Design model. The study involved all 35 learners at the foundation as a total sampling size. Data were collected through a questionnaire based on the Situational Judgment Test (SJT), which demonstrated high reliability (α= 0.842), and complemented by daily behavior observation sheets. Data analysis techniques included descriptive analysis, tendency testing, simple linear regression analysis, and the Paired Sample T-Test. The results indicated that the Canva-based interactive e-book was systematically implemented through preparation, implementation, and evaluation stages via a guided screen-sharing method. Furthermore, statistical analysis confirmed that the implementation of the Canva-based interactive e-book provided a significant contribution, accounting for a 66.4% variance in the improvement of learners' emotional intelligence (Fcount = 68.45, p = 0.000 < 0.05). The Paired Sample T-Test further verified that Ha is accepted (p= 0.000). In conclusion, the implementation of Canva-based interactive e-book media exerts a significant and positive influence on enhancing the emotional intelligence of learners.